Identifikasi Tingkat Keterampilan Bermain Sepak Bola PS. Taruna Desa Potu Kecamatan Dompu Kabupaten Dompu Tahun 2018 - Pratama, Sandi Achmad; Budiman, Budiman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
he level of football playing skills is one aspect of technique that is very influential on the ability of a soccer player in a match. The technical aspects consist of the technique of tilting the ball, passing and holding the ball, heading the ball and shooting towards the goal.This study aims to determine